Social cognition in adolescent girls with fragile X syndrome - Turkstra, Lyn S. (Am J Intellect Dev Disabil, 2014)
This study aimed to characterize social cognition, executive functions (EFs), and everyday social functioning in adolescent girls with fragile X syndrome, and identify relationships among these variables. Participants were 20 girls with FXS and 20 typically developing peers. Results showed significant between-groups differences in social cognition, accounted for by differences in IQ and language. Within the FXS group, IQ and language were related to social cognition; parent-reported social functioning was related to language and EFs; and self-reported social functioning was generally good and not related to cognitive or social cognition variables. Results suggest that intervention might focus on managing language and cognitive contributions to social functioning, rather than social cognition, and underscore the importance of considering parent and adolescent perspectives. (120 words)